Scaling mercury biodynamics from individuals to populations: Implications of an herbivorous fish on mercury cycles in streams. (7th March 2019) - McManamay, Ryan A.; Linam, Franklin; Mathews, Teresa J.; Brooks, Scott C.; Peterson, Mark J.
Abstract: Mercury (Hg) is a widespread environmental pollutant anthropogenically released into aquatic ecosystems where it is tightly retained and cycled through abiotic and biotic processes. Understanding the transport and fate of Hg, including the role of organisms in these cycles, is important. However, few studies, if any, have evaluated the role of macroconsumers in Hg cycling. This requires accounting for organismal regulation of body methylmercury (MeHg) via biodynamics and then scaling individual MeHg concentrations to the population level. Recent evidence suggests that MeHg concentrations will become decrease within an organism as it displays higher growth efficiency (i.e. somatic growth dilution [SGD] concept). However, the implications of individual concentrations, SGD, population size, and individual growth on ecosystem‐level mass‐storage and accumulation of MeHg are uncertain. We examined the influence of population size and individual growth on total MeHg standing stock and accumulation in stoneroller ( Campostoma oligolepis ) populations in a stream contaminated by Hg in east Tennessee, U.S.A. We assessed patterns in periphyton and stoneroller MeHg concentrations in relation to relative growth and population density to determine evidence of SGD and density‐dependent growth, respectively. We simulated the internal regulation of MeHg concentration in stonerollers using a biodynamic model, which was then scaled to the population level to analyse the effects of population density and growth on MeHg standing stock (μg/m 2 ) in stoneroller populations and accumulation rates (i.e. flux, μg m −2 day −1 ) from periphyton communities to stonerollers. MeHg storage and flux in stoneroller populations were compared to standing stocks and methylation rates in periphyton communities. We found evidence of both density‐dependent and density‐independent growth patterns for stonerollers in East Fork Poplar Creek. Stoneroller MeHg concentrations were positively related to periphyton MeHg concentrations; however, evidence of SGD was equivocal. Total MeHg standing stock and accumulation in stoneroller populations was positively related to population density, irrespective of growth. Additionally, higher relative growth was positively related to a higher MeHg accumulation, regardless of density dependence. We found that the standing stock of MeHg in stoneroller populations could be as high as 32× the standing stock of MeHg in periphyton. Finally, the rate of accumulation of MeHg in stonerollers ranged from 5% to over 100% of previously documented methylation rates in periphyton. Our results suggest that abundant macroconsumers may play significant roles in contaminant cycles by mobilising considerable quantities of Hg, storing significant reservoirs of Hg and MeHg, and transferring MeHg to higher trophic levels. Furthermore, the implications of population size and growth of macroconsumers on the storage and flux of MeHg in streams are complicated and dependent upon age structure, density‐dependence, and MeHg concentrations. Our findings suggest that, even though rapid and efficient growth may dilute individual concentrations of contaminants, this may have little influence on ecosystem‐level contaminant fluxes.